2017
DOI: 10.1002/asia.201700437
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Tunable Near‐Infrared and Visible Light Transmittance of MoO3−x Nanocomposites with Different Crystallinity

Abstract: In this Communication, we report MoO nanocomposites in which the near-infrared and visible light transmittance can be selectively modulated through the crystallinity. The MoO nanocomposites were fabricated by a hydrothermal method, and their optical properties were characterized by UV-Vis spectrometer. The obtained results proved the possibility to tune the nanocomposite's optical properties in the UV/Visible spectral region: crystalline MoO mainly regulates the near-infrared range (800-2600 nm), and amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“… Transmittance of a) S1, b) S2, and c) S3 under the same concentration. Reprinted from reference . Copyright 2017 Wiley‐VCH.…”
Section: Amorphous Materials With Lsprmentioning
confidence: 89%
See 1 more Smart Citation
“… Transmittance of a) S1, b) S2, and c) S3 under the same concentration. Reprinted from reference . Copyright 2017 Wiley‐VCH.…”
Section: Amorphous Materials With Lsprmentioning
confidence: 89%
“…It is thus speculated that the effect of crystallinity on their LSPR properties might be significant, as selective tunable solar light is very important for many applications. An example is the work by Li et al . Their study indicated that the different crystallinity of MoO 3− x nanocomposites can have an effect on oxygen deficiencies as well as the plasmon resonance shape and position.…”
Section: Amorphous Materials With Lsprmentioning
confidence: 99%
“…Most work on VO 2 based smart coatings pursue large contrast of optical transmittance in the near infrared region (780-2 500 nm), while inconspicuous contrast in the visible light region (380-780 nm) is desirable for both semiconducting and metallic states. In the solar spectrum, ultraviolet light, visible light and infrared light is responsible for about 7%, 50%, 43% of solar energy, respectively [23]. Therefore, if there is an increased contrast in the visible light region for VO 2 based smart coatings between the semiconducting and the metallic state, relative solar Review on thermochromic vanadium dioxide based smart coatings… 7 modulation ability can be robustly enhanced due to the contribution from the visible light region.…”
Section: Balance Between Luminous Transmittances and Solar Modulationmentioning
confidence: 99%
“…Therefore, smart coatings based on electrochromism [6][7][8][9][10], thermochromism [11][12][13][14][15][16][17][18][19], gasochromism [20][21][22] and photochromism [23][24][25][26] have been widely studied for energy efficient coatings. Thermochromic smart coatings can modulate near-infrared radiation from transmissive to opaque in response to the environmental temperature from low to high, which does not require extra stimuli and can save more energy consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation